Establishment of an efficient one-step enzymatic synthesis of cyclic-2,3-diphosphoglycerate - Stracke, Christina; Meyer, Benjamin H.; De Rose, Simone A.; Ferrandi, Erica Elisa; Kublanov, Ilya V.; Isupov, Michail N.; Harmer, Nicholas J.; Monti, Daniela; Littlechild, Jennifer; Müller, Felix; Snoep, Jacky L.; Bräsen, Christopher; et al. (Frontiers in Microbiology, 2025)
Extremolytes – unique compatible solutes produced by extremophiles - protect biological structures like membranes, proteins, and DNA under extreme conditions, including extremes of temperature and osmotic stress. These compounds hold significant potential for applications in pharmaceuticals, healthcare, cosmetics, and life sciences. However, despite their considerable potential, only a limited number of extremolytes – most notably ectoine and hydroxyectoine – have achieved commercial relevance, primarily due to the absence of efficient production strategies for the majority of other extremolytes. Cyclic 2,3-diphosphoglycerate (cDPG), a unique metabolite found in certain hyperthermophilic methanogenic Archaea, plays a key role in thermoprotection and is synthesized from 2-phosphoglycerate (2PG) through a two-step enzymatic process involving 2-phosphoglycerate kinase (2PGK) and cyclic-2,3-diphosphoglycerate synthetase (cDPGS). In this study, we present the development of an efficient in vitro enzymatic approach for the production of cDPG directly from 2,3-diphosphoglycerate (2,3DPG), leveraging the activity of the cDPGS from Methanothermus fervidus (MfcDPGS). We optimized the heterologous production of MfcDPGS in Escherichia coli by refining codon usage and expression conditions. The purification process was significantly streamlined through an optimized heat precipitation step, coupled with effective stabilization of MfcDPGS for both usage and storage by incorporating KCl, Mg2+, reducing agents and omission of an affinity tag. The recombinant MfcDPGS showed a Vmax of 38.2 U mg−1, with KM values of 1.52 mM for 2,3DPG and 0.55 mM for ATP. The enzyme efficiently catalyzed the complete conversion of 2,3DPG to cDPG. Remarkably, even at a scale of 100 mM, it achieved full conversion of 37.6 mg of 2,3DPG to cDPG within 180 min, using just 0.5 U of recombinant MfcDPGS at 55°C. These results highlight that MfcDPGS can be easily produced, rapidly purified, and sufficiently stabilized while delivering excellent conversion efficiency for cDPG synthesis as value added product. Additionally, a kinetic model for MfcDPGS activity was developed, providing a crucial tool to simulate and scale up cDPG production for industrial applications. This streamlined process offers significant advantages for the scalable synthesis of cDPG, paving the way for further biochemical and industrial applications of this extremolyte.